A climate model-based long-term capacity forecast of the Northern Sea Route - Solakivi, Tomi; Hellström, Rasmus; Uotila, Petteri; Ojala, Lauri (Springer Nature, 2026)
This article estimates the future transit capacity of the Northern Sea Route (NSR) in consideration of the ice navigation capabilities of the world fleet and the escort capacity of the current and planned Russian icebreakers. The work employs two different storyline simulations from the Coupled Model Intercomparison Project Phase 6 (CMIP6) to account for the future development of sea ice extent and thickness between 2024 and 2050. In both simulations, the transit traffic is expected to remain seasonal and highly dependent on limited icebreaking capacity, affecting the potential of liner shipping in particular. In the analyzed simulations, the current and estimated maximum transit capacity of the NSR significantly exceeds currently realized transport volumes, confirming prior assumptions that volumes on the route are not a capacity issue but are instead mostly caused by a lack of time savings, poor economic viability, and navigational safety concerns.